Assessment of Perioperative Blood Glucose Levels in Various Anaesthetic Techniques in Non-Diabetics Versus Diabetics Undergoing Lower Abdominal and Lower Limb Surgery - Rohini, Rohini; Agarwal, Shilpi; Shaboo, Surekha; Goel, Manika (Journal of Neonatal Surgery, 2025)
Background:For many years, there has been a great deal of analysis and debate over the hormonal and metabolic response to anesthesia and surgery. The present study was conducted to assess perioperative blood glucose levels in various anaesthetic techniques in non-diabetics and diabetics. Materials & Methods: 120 ASA grade I/ II subjects of both genders were divided into 2 groups of 60 each. Group I were diabetics and group II were non- diabetics. All were managed under either general anaesthesia, epidural anesthesia and spinal anesthesia. 5 ml of venous blood was taken and assessed for fasting blood sugar, random blood glucose and glycated hemoglobin level by an autoanalyzer (911 HITACHI AUTO ANALYSER)preoperatively, after intubation / after achieving T6 segment in regional anaesthesia cases followed by samples at 20, 40 and 60 minutes. Postoperatively two samples at 20, and 40 minutes. Results: There were 10 males and 10 females, 11 males and 9 females and 8 males and 12 females in patients undergoing general anaesthesia, epidural anesthesia and spinal anesthesia respectively. The mean weight was 52.4 kgs, 56.1 kgs and 55.6 kgs in patients undergoing general anaesthesia, epidural anesthesia and spinal anesthesia respectively. The difference was non- significant (P> 0.05). The mean blood glucose level in group I was 114.2 mg/dl and in group II was 88.6 mg/dl under general anesthesia. The mean blood glucose level in group I was 124.6 mg/dl and in group II was 94.2 mg/dl under epidural anesthesia. The mean blood glucose level in group I was 112.8 mg/dl and in group II was 96.4 mg/dl under spinal anesthesia. The difference was significant (P< 0.05). The mean blood glucose rise in group I and group II was 40.2% and 31.5% under general anaesthesia, 19.4% and 14.2% under epidural anesthesia and 11.2% and 7.2% under spinal anesthesia. The difference was significant (P< 0.05). Conclusion: The degree of rising of blood sugar due to surgical stress is highest in general anaesthesia as compared to other techniques and still higher in controlled diabetics as compared to non diabetics.. When feasible, localized treatments can reduce a diabetic's response to surgical stress. It may not be necessary to follow an intraoperative insulin regimen for every operation; rather, it relies more on how long and how severe the procedure is.